2007
DOI: 10.1007/s00068-007-7124-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Spinal and Associated Injuries in Multiple Trauma Patients

Abstract: Injury to the spinal column and cord are often part of life-threatening multiple trauma. Epidemiological data could help to establish an evidence-based assessment and therapy of these patients. We present a retrospective chart analysis of 590 multiple traumatized patients admitted within a 4-year-period. Patients suffering from injuries of the spinal column were analysed regarding mechanism and distribution of their injuries to all body regions. Thirty-one percent (n = 183) of polytraumatized patients displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
3
24
2
1
Order By: Relevance
“…In total, the proportion that we observed for the total number of type A fractures was considerably higher than that reported by Leucht et al 2 As for neurological lesions, the incidence is similar to that reported by Leucht et al, 2 Chu et al, 3 and Laurer et al 1 (24.7%, 27.6%, and 24.6% respectively), and the distribution by Frankel classification, in total, is similar to that reported previously. The distribution by segment according to the Frankel classification is relatively uniform for Frankel E.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In total, the proportion that we observed for the total number of type A fractures was considerably higher than that reported by Leucht et al 2 As for neurological lesions, the incidence is similar to that reported by Leucht et al, 2 Chu et al, 3 and Laurer et al 1 (24.7%, 27.6%, and 24.6% respectively), and the distribution by Frankel classification, in total, is similar to that reported previously. The distribution by segment according to the Frankel classification is relatively uniform for Frankel E.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of injury mechanisms, Leucht et al 2 divide falls into high--energy and low-energy, the former causing 39% of the injuries and the latter causing 20%, as different from Anwar, 4 who reports motor vehicle accidents in first place at 37.4%, falls at 24% (falls from heights), and falling down the stairs at 12.6%. On the other hand, Laurer et al 1 report automobile accidents at 31%, motorcycles at 12%, and falls at a total of 40%. We observed results similar to those of Leucht et al, 2 with the combined percentage of falls at 63.16%, followed by motor vehicle accidents at 21.05%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine included studies were conducted in the USA [2,7,9,15,16,21,28,33,34]; 3 in the UK [1,12,19]; 2 in China [41,47]; and 1 in each of Pakistan [30], Taiwan [6], Australia [27], South Africa [37], Japan [23], Germany [24], and Canada [35]. Studies were not excluded based on publication year.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…6 In the global scenario, Laurer et al stated that there is a correlation between age, sex, and the cause of the accident and the type and distribution of the fractures, as well as the number of spine fractures that occur with associated injuries, extremely useful information for improving diagnostic and patient care protocols. 7 Despite the vast knowledge of biomechanics and spinal stability, little is known at the global and national levels about the epidemiology of these injuries, which is why it is important to highlight the growing problem that it represents in our country, as reported in a study conducted at the Hospital de Traumatología y Ortopedia de Lomas Verdes in the state of Mexico, in which most of these injuries were secondary to falls from heights, followed by traffic accidents. The lumbar spine was the most affected segment in this series, with 76% of the patients with neurological involvement upon arrival at emergency services, 8 highlighting the key points in which a culture of prevention could have an impact in reducing these injuries and their sequelae.…”
Section: Introductionmentioning
confidence: 99%